2021
DOI: 10.3389/fpsyg.2021.773749
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Regulations on Trade Flows: A Focus on Environmental Goods Listed in APEC and OECD

Abstract: This paper aims to investigate the impact of environmental regulations on trade patterns, in terms of trade in environmental goods listed in Asia-Pacific Economic Cooperation (APEC) and Organization for Economic Co-operation and Development (OECD). Environmental goods are defined here as those that enable sustainable growth and reduce pollution from human activity. For this reason, issues on environmental goods can be put at the forefront to analyze the linkage between environmental regulations and trade flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In contrast, Dai et al (2021) applied the gravity model and the z-score to examine the trade-environmental regulation nexus in 112 exporting countries and 53 importing countries over the period 1989-2013. Their findings revealed that the strict environmental policies harm trade.…”
Section: Trade Openness and Co 2 Emission Literaturementioning
confidence: 99%
“…In contrast, Dai et al (2021) applied the gravity model and the z-score to examine the trade-environmental regulation nexus in 112 exporting countries and 53 importing countries over the period 1989-2013. Their findings revealed that the strict environmental policies harm trade.…”
Section: Trade Openness and Co 2 Emission Literaturementioning
confidence: 99%
“…However, Liu and Zhou (2010) argued that environmental taxes had a negative impact on employment and economic growth. Similarly, Dai et al (2021)found that environmental regulations affected trade. Adopting a CGE model to test, Carbon taxation could achieve a "double dividend" and encourage investment (Orlov and Grethe, 2012).…”
Section: Environmental Tax and Double Dividendmentioning
confidence: 99%
“…Two different views exist in parallel. In the traditional view, environmental regulations impose various restrictions on companies' existing pollutant discharge behaviors, which inevitably lead to increased costs for companies, thereby reducing corporate profits and performance (Rassier and Earnhart, 2010;Greenstone et al, 2012;Dai et al, 2021). Some studies have supported this view (Yu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%